PENGARUH KARAKTERISTIK IBU DAN DUKUNGAN SUAMI TERHADAP PEMERIKSAAN KEHAMILAN DI KECAMATAN ANGKOLA TIMUR KABUPATEN TAPANULI SELATAN - Harahap, Rosmawaty; Siregar, Meidiawaty (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2014)
One of the efforts to observe the progress of pregnancy in order to ascertain good health of the motherand the womb is by getting antenatal care. The result of the preliminary survey in working area ofHealth Centre Pargarutan, East Angkola district showed that according to the data 2009, the coverageof K4 was 73,5% and the data 2010, the coverage of K4 was only 78% (it is still far from the expectedcoverage by Ministry of Health , that 90%). This research was aimed to analyze the influence of thecharacteristics of the mother (parity, age, occupation, education) and husband’s support (informational,assessment, instrumental and emotional) on antenatal care. The type of the research was cross-sectionalstudy. The research was carried out in Health Centre Pargarutan, East Angkola district. The populationin this research were all pregnant women in Health Centre Pargarutan, East Angkola district with KIAbook. The amount of the sample were 74 pregnant women with proportional sampling technique. Dataanalysis used multiple logistic regression test with significance level of 95% ( α < 0,05). The result ofthe research showed that there were influences of parity, emotional support and instrumental support onantenatal care. There was no influence of mother’s age, education, occupation, informational support andassessment/appreciation support on antenatal care. The most dominant variable influenced on antenatalcare was emotional support. It is recommended that the policy-maker should conduct cooperation in orderto improve the routine socialization and counseling on the antenatal care with involve the pregnantmother’s husbands to accompany them.